Electro-hydraulic fragmentation vs conventional crushing of photovoltaic panels – Impact on recycling. (15th March 2019) - Nevala, Sanna-Mari; Hamuyuni, Joseph; Junnila, Tero; Sirviö, Tuomas; Eisert, Stefan; Wilson, Benjamin P.; Serna-Guerrero, Rodrigo; Lundström, Mari
Highlights: Solar panels can be effectively dismantled by Electro-Hydraulic Fragmentation (EHF). Both crushing and EHF produce a wide fraction distribution between <0.25 to >4 mm. Crushing followed by sieving results in a high level of metals in all fractions. EHF and sieving concentrates metal elements into two main fractions <0.5 and >4 mm. Over 98% of Cu in a PV panel is found in the >4 mm fraction produced by impulse EHF. Abstract: Currently, the first generation of solar panels are reaching their end-of-life, however so far, there is no best available technology (BAT) to deal with solar panel waste in terms of the optimized circular economy of metals. In this brief communication, electro-hydraulic fragmentation (EHF) is explored as an initial conditioning stage of photovoltaic (PV) modules to facilitate the recovery of valuable metals with the main goal to produce liberated fractions that are suitable for the retrieval of materials like Si, Ag, Cu, Sn, Pb, and Al. When compared to traditional crushing, the results suggest that dismantling of PV panels using EHF shows more selectivity by concentrating metals among well-defined particle size fractions. Using this method, the subsequent recovery of metals from PV panels can be achieved in a straightforward manner by simple means like sieving. The fragmentation achievable with EHF technology allowed approximately 99% Cu, 60% Ag, 80% of Pb, Sn and Al total elemental weight within the solar panels to be concentrated solely within the >4 mm size range, whereas high purity (>99%) Si could be found in the fractions between >0.50 mm and <2 mm. To the best of the authors' knowledge, this paper presents for the first time a comparative analysis on the use of EHF technique and conventional crushing for the processing of PV solar panel waste.